2014
DOI: 10.1177/0954405414528165
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment in hard turning of AISI 1015 steel under spray impingement cooling and dry environment

Abstract: This work investigates the effects of cutting parameters on surface roughness (Ra, µm), cutting temperature (T, °C) at the chip–tool interface and the material removal rate during hard machining of AISI 1015 (43 ± 1 HRC) steel using carbide insert under dry and spray impingement cooling environment. A combined technique using orthogonal array and analysis of variance was employed to investigate the contribution of spindle speed, feed rate, depth of cut and air pressure on responses. It is observed that with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…The experimental results show that average surface roughness are low at higher depth of cut but at a slower rate for which it can be considered as less affecting parameter for surface roughness in the studied range, which could be used to improve productivity if it would not worsen the surface microstructure. Similar observations are reported by Sahu et al (2014). Figure 4(a) and (b) displays the SEM images of the poor and best surface texture quality attained by the interaction between AISI 4340 hardened steel and multilayer (TiN/ TiCN/Al 2 O 3 /TiN) coated carbide tool using various cutting conditions.…”
Section: Surface Roughness Analysissupporting
confidence: 79%
“…The experimental results show that average surface roughness are low at higher depth of cut but at a slower rate for which it can be considered as less affecting parameter for surface roughness in the studied range, which could be used to improve productivity if it would not worsen the surface microstructure. Similar observations are reported by Sahu et al (2014). Figure 4(a) and (b) displays the SEM images of the poor and best surface texture quality attained by the interaction between AISI 4340 hardened steel and multilayer (TiN/ TiCN/Al 2 O 3 /TiN) coated carbide tool using various cutting conditions.…”
Section: Surface Roughness Analysissupporting
confidence: 79%
“…Because of this, focus on application of environmental conscious lubricating system in hard turning is emerging. Some techniques like minimum quantity lubrication (MQL), high pressure cutting fluid application, and spray impingement cooling are emerging as improved cutting fluid techniques compared to flooded cooling and dry surroundings which were reported by various researchers (Chinchanikar & Choudhury, 2015;Sharma et al, 2014;Sahu et al, 2015;Mishra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sahoo et al (2017), while dry turning Al 63400 alloy, applied WPCA along with response surface methodology to investigate the optimized parameters for machined surface roughness and cutting tool vibration; and reported the combination of 600 rpm (spindle speed), 25 mm/min (feed rate) and 0.2 mm (depth of cut) were the optimal parameters for the quality targets. Sahu et al (2015), while turning AISI 1015 steel with carbide inserts observed improved cutting performance with respect to surface quality, cutting temperature and rate of material removal in the SIC environment than those with the dry environment. In our previous work , use of SIC environment for turning the as cast AMC with uncoated carbide inserts also proved beneficial.…”
Section: Introductionmentioning
confidence: 87%